2006
DOI: 10.1080/09638180500252078
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of corporate annual financial reporting in Greece

Abstract: This paper reports on the results of an empirical investigation of the factors that affect timely annual financial reporting practices by 95 non-financial, group companies listed on the Athens Stock Exchange. A descriptive analysis indicates that 92% of the companies reported early (relative to the 161-day regulatory deadline), 3% reported on the 161st day and 5% reported late. A multivariate regression analysis suggests that large companies, service companies and companies audited by the former Big-5 audit fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
93
6
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 18 publications
17
93
6
12
Order By: Relevance
“…The majority of related studies were conducted in the USA and other Anglo-Saxon institutional settings [1,5,6,8,9,15,16]. However, in the recent years the issue has also become popular in other countries with dierent institutional and regulatory settings, like Malaysia [7], China [19], Greece [21], Spain [4], Turkey [23], etc. A great interest in researching this issue on international level additionally emphasizes its relevance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of related studies were conducted in the USA and other Anglo-Saxon institutional settings [1,5,6,8,9,15,16]. However, in the recent years the issue has also become popular in other countries with dierent institutional and regulatory settings, like Malaysia [7], China [19], Greece [21], Spain [4], Turkey [23], etc. A great interest in researching this issue on international level additionally emphasizes its relevance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though regulatory bodies impose certain requirements regarding the nancial reporting timeliness, considerable discretion still remains within the regulatory framework. Timely reporting in emerging markets is of particular importance since in these markets information is relatively limited and has a longer time lag [21]. Also, according to the McGee and Yuan [19], there is evidence that companies in transition economies issue their nancial statements much later than companies in more developed market economies.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has also been used in other empirical studies in developing economies (Guidara et al, 2014 in South Africa and Owusu-Ansah & Leventis, 2006 in Greece). According to Owusu-Ansah and Leventis (2006), this date represents a good proxy for the publication date of financial statements, because companies are allowed to publish their annual reports and earnings following the certification of financial statements by an independent auditor.…”
Section: Timely Disclosurementioning
confidence: 99%
“…In this study, earnings announcement lag is measured in terms of the lapse of time between a companies' fiscal year-end and the date when financial statements are certified by auditor (Leventis & Owusu-Ansah, 2006). Prior studies reported timely information is very important (see, for example, Chambers & Penman, 1984;Begley & Fischer, 1998).…”
Section: Earnings Announcement Lag and The Cost Of Debtmentioning
confidence: 99%
“…Publication date is approximated by the date of issuance of the audit report (signature of the report). This date is a good proxy because companies will not delay the publication of their financial reports after the financial statements have been audited (Leventis & Owusu-Ansah, 2006).…”
Section: Earnings Announcement Lagmentioning
confidence: 99%